multiply:(x2+xy)(x2-xy)
Answers
Answered by
1
Using identity (a+b)(a-b) = a^2 - b^2
![( {x}^{2} + xy)( {x}^{2} - xy) \\ \\ = ( { {x}^{2} )}^{2} - {(xy)}^{2} \\ \\ = {x}^{4} - {x}^{2} {y}^{2} ( {x}^{2} + xy)( {x}^{2} - xy) \\ \\ = ( { {x}^{2} )}^{2} - {(xy)}^{2} \\ \\ = {x}^{4} - {x}^{2} {y}^{2}](https://tex.z-dn.net/?f=%28+%7Bx%7D%5E%7B2%7D++%2B+xy%29%28+%7Bx%7D%5E%7B2%7D++-+xy%29+%5C%5C++%5C%5C++%3D+%28+%7B+%7Bx%7D%5E%7B2%7D+%29%7D%5E%7B2%7D++-++%7B%28xy%29%7D%5E%7B2%7D++%5C%5C++%5C%5C++%3D++%7Bx%7D%5E%7B4%7D++-++%7Bx%7D%5E%7B2%7D++%7By%7D%5E%7B2%7D+)
Answered by
0
four x square minusxsquare y square
Similar questions